Prooxidant/antioxidant ratio (ProAntidex) as a better index of net free radical scavenging potential - Ling, L.T.; Palanisamy, U.D.; Cheng, H.M. (MDPI AG, 2010)
The antioxidant activity of several Malaysian plant extracts was analyzed simultaneously with their pro-oxidant capacity. This ratio represents an index (ProAntidex) of the net free radical scavenging ability of whole plant extracts. We observed that ethanolic extracts of Nephelium lappaceum peel, Fragaria x ananassa leaf, Lawsonia inermis leaf, Syzygium aqueum leaf and grape seed had a lower Pro-Antidex than the commercially available Emblica (TM) extract which is an antioxidant agent with very low prooxidant activity. Among the aqueous extracts, Lawsonia inermis leaf, Nephelium mutobile leaf and grape seed had lower pro-oxidant activity compared to the Emblica (TM) extract. Among these extracts, aqueous extract of Nephelium mutobile leaf had a very low index of 0.05 compared to 0.69 for Emblica (TM). Most of the extracts had a far lower ProAntidex compared to the Vitamin C. The index enables us to identify extracts with high net free radical scavenging activity potential. The ProAntidex is beneficial as a screening parameter to the food industries and healthcare.